2011
DOI: 10.1179/1743288x11y.0000000028
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of non-specific arm pain

Abstract: Background: Non-specific arm pain (NSAP) is a vague clinical entity which may constitute up to 53% of work related upper limb disorders. The pathophysiology of NSAP is poorly understood with hypotheses ranging from disturbance of muscle function and neuropathic arm pain to central sensitization.Objectives: The purpose of this review was to investigate the current level of evidence to support three main classifications of pain (peripheral neuropathic pain, nociceptive pain and central sensitization) in NSAP. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…1,2 It is defined as diffuse pain in the forearm, which can also involve the neck, upper arm, wrist, and hand, in the absence of evidence of a specific disorder. [4][5][6] Previous studies of NSAP have identified hyperalgesia in response to clinical tests of neural tissue sensitivity. [4][5][6] Previous studies of NSAP have identified hyperalgesia in response to clinical tests of neural tissue sensitivity.…”
mentioning
confidence: 99%
“…1,2 It is defined as diffuse pain in the forearm, which can also involve the neck, upper arm, wrist, and hand, in the absence of evidence of a specific disorder. [4][5][6] Previous studies of NSAP have identified hyperalgesia in response to clinical tests of neural tissue sensitivity. [4][5][6] Previous studies of NSAP have identified hyperalgesia in response to clinical tests of neural tissue sensitivity.…”
mentioning
confidence: 99%
“…Some people also experience pain in the forearm that is undiagnosed and is described as having ‘non‐specific arm pain’, previously known as repetitive strain injury. 2 The prevalence of DUL‐MSDs varies with the specific disorder, with hand OA affecting 27% of the population, 3 carpal tunnel syndrome affecting between 1% and 16% 4 , 5 and tenosynovitis and epicondylitis affecting between 1% and 3%. 6 , 7 MSDs account for 21% of years living with a disability, a measure that considers the prevalence of the disease and how disabling the disease is.…”
Section: Introductionmentioning
confidence: 99%
“…Common DUL‐MSDs include hand and thumb osteoarthritis (OA), epicondylitis, tenosynovitis and carpal tunnel syndrome. Some people also experience pain in the forearm that is undiagnosed and is described as having ‘non‐specific arm pain’, previously known as repetitive strain injury 2 . The prevalence of DUL‐MSDs varies with the specific disorder, with hand OA affecting 27% of the population, 3 carpal tunnel syndrome affecting between 1% and 16% 4,5 and tenosynovitis and epicondylitis affecting between 1% and 3% 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Various classifications of these exist, such as nociceptive pain, peripheral neuropathic pain and central sensitisation. Moloney et al 6 provide a review of the evidence for these mechanisms for patient presenting with non-specific arm pain. It is often seen in clinical practice that patients present with symptom patterns indicating central sensitization, in addition to more defined nociceptive pain.…”
mentioning
confidence: 99%